The Recurrence of Venous Thromboembolism in Obstructive Sleep Apnea: A Narrative Review - Mohsen Gholinataj Jelodar; Besharat Rahimi; Samaneh Mirzaei (Canadian Respiratory Journal)
Venous thromboembolism (VTE) is widespread and poses significant risks of illness and death, making it a vital public health issue. Obstructive sleep apnea (OSA), which is the most prevalent sleep disorder, is connected to an increased possibility of cardiovascular diseases and VTE. The length of VTE treatment hinges mainly on the frequency of its recurrence in patients. Our data about VTE and its recurrence in OSA patients are limited. In this review, we aim to investigate the risk of VTE recurrence in OSA patients and evaluate the role of continuous positive airway pressure (CPAP) therapy in mitigating this risk. A literature search gathered information about VTE pathogenesis and its potential recurrence mechanism in OSA. The recurrent episodes of partial or complete obstruction of the upper airway in OSA lead to intermittent lack of oxygen. Hypoxemia acts as a central cornerstone of VTE incidence in OSA patients, leads to activating all the vertices of Virchow’s triad, and creates the appropriate condition for the developmental and even recurrence of VTE. Intermittent hypoxia causes an increase in the inflammatory state and coagulation activity, leading to oxidative stress and endothelial dysfunction. Furthermore, it results in heightened viscosity and venous stasis. The results of previous studies on VTE recurrence in OSA patients are conflicting. Even though the use of CPAP leads to diminished proinflammatory cytokines and oxidative stress indicators, there is currently insufficient clinical evidence to support that this therapy can prevent recurrent VTE in patients with OSA. Further investigation is necessary to gain a better comprehension of the probability and frequency of relapse of VTE in OSA patients, as the present research has generated inconclusive outcomes.